The sequel to COVID-19: the antithesis to life - Sudhir Bhandari; Ajit Singh Shaktawat; Bhoopendra Patel; Amitabh Dube; Shivankan Kakkar; Amit Tak; Jitendra Gupta; Govind Rankawat (Journal of Ideas in Health, 2020)
The pandemic of COVID-19 has afflicted every individual and has initiated a cascade of directly or indirectly involved events in precipitating mental health issues. The human species is a wanderer and hunter-gatherer by nature, and physical social distancing and nationwide lockdown have confined an individual to physical isolation. The present review article was conceived to address psychosocial and other issues and their aetiology related to the current pandemic of COVID-19. The elderly age group has most suffered the wrath of SARS-CoV-2, and social isolation as a preventive measure may further induce mental health issues. Animal model studies have demonstrated an inappropriate interacting endogenous neurotransmitter milieu of dopamine, serotonin, glutamate, and opioids, induced by social isolation that could probably lead to observable phenomena of deviant psychosocial behavior. Conflicting and manipulated information related to COVID-19 on social media has also been recognized as a global threat. Psychological stress during the current pandemic in frontline health care workers, migrant workers, children, and adolescents is also a serious concern. Mental health issues in the current situation could also be induced by being quarantined, uncertainty in business, jobs, economy, hampered academic activities, increased screen time on social media, and domestic violence incidences. The gravity of mental health issues associated with the pandemic of COVID-19 should be identified at the earliest. Mental health organization dedicated to current and future pandemics should be established along with Government policies addressing psychological issues to prevent and treat mental health issues need to be developed. References World Health Organization (WHO) Coronavirus Disease (COVID-19) Dashboard. Available at: https://covid19.who.int/ [Accessed on 23 August 2020] Sim K, Chua HC. The psychological impact of SARS: a matter of heart and mind. CMAJ. 2004; 170:811e2. https://doi.org/10.1503/cmaj.1032003. Wu P, Fang Y, Guan Z, Fan B, Kong J, Yao Z, et al. The psychological impact of the SARS epidemic on hospital employees in China: exposure, risk perception, and altruistic acceptance of risk. Can J Psychiatr. 2009; 54:302e11. https://doi.org/10.1177/070674370905400504. Brooks SK, Webster RK, Smith LE, Woodland L, Wessely S, Greenberg N, et al. The psychological impact of quarantine and how to reduce it: rapid review of the evidence. Lancet. 2020; 395:912e20. https://doi.org/10.1016/S0140-6736(20)30460-8. Robertson E, Hershenfield K, Grace SL, Stewart DE. The psychosocial effects of being quarantined following exposure to SARS: a qualitative study of Toronto health care workers. Can J Psychiatr. 2004; 49:403e7. https://doi.org/10.1177/070674370404900612. Barbisch D, Koenig KL, Shih FY. Is there a case for quarantine? Perspectives from SARS to Ebola. Disaster Med Public Health Prep. 2015; 9:547e53. https://doi.org/10.1017/dmp.2015.38. Jeong H, Yim HW, Song YJ, Ki M, Min JA, Cho J, et al. Mental health status of people isolated due to Middle East Respiratory Syndrome. Epidemiol Health. 2016;38: e2016048. https://doi.org/10.4178/epih.e2016048. Liu X, Kakade M, Fuller CJ, Fan B, Fang Y, Kong J, et al. Depression after exposure to stressful events: lessons learned from the severe acute respiratory syndrome epidemic. Compr Psychiatr. 2012; 53:15e23. https://doi.org/10.1016/j.comppsych.2011.02.003 Chadda RK, Deb KS. Indian family systems, collectivistic society and psychotherapy. Indian J Psychiatry. 2013;55: S299‑ https://dx.doi.org/10.4103%2F0019-5545.105555. Grover S, Sahoo S, Mehra A, Avasthi A, Tripathi A, Subramanyan A, et al. Psychological impact of COVID‑19 lockdown: An online survey from India. Indian J Psychiatry. 2020; 62:354-62. https://doi.org/ 10.4103/psychiatry.IndianJPsychiatry _427_20. Hawkley LC, Cacioppo JT. Loneliness matters: a theoretical and empirical review of consequences and mechanisms. Ann Behav Med. 2010; 40: 218–27. https://dx.doi.org/10.1007%2Fs12160-010-9210-8. Chen N, Zhou M, Dong X, Qu J, Gong F, Han Y, et al. Epidemiological and clinical characteristics of 99 cases of 2019 novel coronavirus pneumonia in Wuhan, China: a descriptive study. Lancet. 2020;395(10223):507-13. https://doi.org/10.1016/S0140-6736(20)30211-7. Bhandari S, Sharma R, Singh Shaktawat A, Banerjee S, Patel B, Tak A, et al. COVID-19 related mortality profile at a tertiary care centre: a descriptive study. Scr Med. 2020;51(2):69-73. https://doi.org/10.5937/scriptamed51-27126. Baumeister RF, Leary MR. The need to belong: desire for interpersonal attachments as a fundamental human motivation. Psychol Bull. 1995; 117: 497–529. https://doi.org/10.1037/0033-2909.117.3.497. Caspi A, Harrington H, Moffitt TE, Milne BJ, Poulton R. Socially isolated children 20 years later: risk of cardiovascular disease. Arch Pediatr Adolesc Med. 2006; 160(8):805-11. https://doi.org/10.1001/archpedi.160.8.805. Eaker ED, Pinsky J, Castelli WP. Myocardial infarction and coronary death among women: psychosocial predictors from a 20-year follow-up of women in the Framingham Study. Am J Epidemiol. 1992; 135(8):854-64. https://doi.org/10.1093/oxfordjournals.aje.a116381. Luo Y, Hawkley LC, Waite LJ, Cacioppo JT. Loneliness, health, and mortality in old age: a national longitudinal study. Soc Sci Med. 2012 Mar; 74(6):907-14. https://dx.doi.org/10.1016%2Fj.socscimed.2011.11.028. Olsen RB, Olsen J, Gunner-Svensson F, Waldstrøm B. Social networks and longevity. A 14-year follow-up study among elderly in Denmark. Soc Sci Med. 1991; 33(10):1189-95. https://doi.org/10.1016/0277-9536(91)90235-5. Patterson AC, Veenstra G. Loneliness and risk of mortality: a longitudinal investigation in Alameda County, California. Soc Sci Med. 2010; 71(1):181-6. https://doi.org/10.1016/j.socscimed.2010.03.024. Savikko N, Routassalo P, Tilvis RS, Strandberg TE, Pitkalla KH. Predictors and subjective causes of loneliness in an aged population. Arch Gerontol Geriatrics. 2005; 41:3;223-33. https://doi.org/10.1016/j.archger.2005.03.002. Health Advisory for Elderly Population of India during COVID19. Available at: https://www.mohfw.gov.in/pdf/AdvisoryforElderlyPopulation.pdf [Accessed on 13 August 2020]. Dicks D, Myers R, Kling A. Uncus and amygdala lesions: effects on social behavior in the free-ranging rhesus monkey. Science. 1969; 165:69–71. https://doi.org/10.1126/science.165.3888.69. Kanai R, Bahrami B, Duchaine B, Janik A, Banissy MJ, Rees G. Brain structure links loneliness to social perception. Curr Biol. 2012; 22(20):1975-9. https://dx.doi.org/10.1016%2Fj.cub.2012.08.045. Bender AR, Daugherty A, Raz N. Vascular risk moderates associations between hippocampal subfield volumes and memory. J Cogn Neurosci. 2013; 25:1851–62. https://doi.org/10.1162/jocn_a_00435. Raz N. Diabetes: brain, mind, insulin–what is normal and do we need to know? Nat Rev Endocrinol. 2011; 7:636–7. https://doi.org/10.1038/nrendo.2011.149. Colcombe SJ, Erickson KI, Naftali R, Andrew GW, Cohen NJ, McAuley E, et al. Aerobic fitness reduces brain tissue loss in aging humans. J Gerontol A Biol Sci Med Sci. 2003; 58:176–80. https://doi.org/10.1093/gerona/58.2.m176. Maass A, Düzel S, Goerke M, Becke A, Sobieray U, Neumann K, et al. Vascular hippocampal plasticity after aerobic exercise in older adults. Mol Psychiatry. 2015; 20, 585–93. https://doi.org/10.1038/mp.2014.114. Wilson RS, Krueger KR, Arnold SE, Schneider JA, Kelly JF, Barnes LL, et al. Loneliness and Risk of Alzheimer Disease. Arch Gen Psychiatry. 2007;64(2):234–240. https://doi.org/10.1001/archpsyc.64.2.234. Kogan JH, Frankland PW, Silva AJ. Long-term memory underlying hippocampus-dependent social recognition in mice. Hippocampus. 2000;10(1):47-56. https://doi.org/10.1002/(sici)1098-1063(2000)10:1%3C47::aid-hipo5%3E3.0.co;2-6. Yorgason JT, España RA, Konstantopoulos JK, Weiner JL, Jones SR. Enduring increases in anxiety-like behavior and rapid nucleus accumbens dopamine signaling in socially isolated rats. Eur J Neurosci. 2013;37(6):1022-31. https://doi.org/10.1111/ejn.12113. Bledsoe AC, Oliver KM, Scholl JL, Forster GL. Anxiety states induced by post-weaning social isolation are mediated by CRF receptors in the dorsal raphe nucleus. Brain Res Bull. 2011;85(3-4):117-22. https://dx.doi.org/10.1016%2Fj.brainresbull.2011.03.003. Lukkes JL, Engelman GH, Zelin NS, Hale MW, Lowry CA. Post-weaning social isolation of female rats, anxiety-related behavior, and serotonergic systems. Brain Res. 2012; 1443:1-17. https://dx.doi.org/10.1016%2Fj.brainres.2012.01.005. Ago Y, Araki R, Tanaka T, Sasaga A, Nishiyama S, Takuma K, et al. Role of social encounter-induced activation of prefrontal serotonergic systems in the abnormal behaviors of isolation-reared mice. Neuropsychopharmacology. 2013; 38(8):1535-47. https://doi.org/10.1038/npp.2013.52. Veenema AH. Early life stress, the development of aggression and neuroendocrine and neurobiological correlates: what can we learn from animal models? Front Neuroendocrinol. 2009;30(4):497-518. https://doi.org/10.1016/j.yfrne.2009.03.003. Zhao X, Sun L, Jia H, Meng Q, Wu S, Li N, et al. Isolation rearing induces social and emotional function abnormalities and alters glutamate and neurodevelopment-related gene expression in rats. Prog Neuropsychopharmacol Biol Psychiatry. 2009;33(7):1173-1177. https://doi.org/10.1016/j.pnpbp.2009.06.016. Sciolino NR, Bortolato M, Eisenstein SA, Fu J, Oveisi F, Hohmann AG, et al. Social isolation and chronic handling alter endocannabinoid signaling and behavioral reactivity to context in adult rats. Neuroscience. 2010;168(2):371-86. https://dx.doi.org/10.1016%2Fj.neuroscience.2010.04.007. Ghasemi M, Phillips C, Trillo L, De Miguel Z, Das D, Salehi A. The role of NMDA receptors in the pathophysiology and treatment of mood disorders. Neurosci Biobehav Rev. 2014; 47:336-358. https://doi.org/10.1016/j.neubiorev.2014.08.017. Olivenza R, Moro MA, Lizasoain I, Lorenzo P, Fernández AP, Rodrigo J, et al. Chronic stress induces the expression of inducible nitric oxide synthase in rat brain cortex. J Neurochem. 2000;74(2):785-791. https://doi.org/10.1046/j.1471-4159.2000.740785.x. Maeng S, Zarate CA Jr, Du J, Schloesser RJ, McCammon J, Chen G, et al. Cellular mechanisms underlying the antidepressant effects of ketamine: role of alpha-amino-3-hydroxy-5-methylisoxazole-4-propionic acid receptors. Biol Psychiatry. 2008;63(4):349-352. https://doi.org/10.1016/j.biopsych.2007.05.028. Kalia LV, Kalia SK, Salter MW. NMDA receptors in clinical neurology: excitatory times ahead. Lancet Neurol. 2008;7(8):742-755. https://dx.doi.org/10.1016%2FS1474-4422(08)70165-0. Waxman EA, Lynch DR. N-methyl-D-aspartate Receptor Subtypes: Multiple Roles in Excitotoxicity and Neurological Disease. The Neuroscientist. 2005; 11(1), 37–49. https://doi.org/10.1177/1073858404269012. Hermes G, Li N, Duman C, Duman R. Post-weaning chronic social isolation produces profound behavioral dysregulation with decreases in prefrontal cortex synaptic-associated protein expression in female rats. Physiol Behav. 2011;104(2):354-9. https://dx.doi.org/10.1016%2Fj.physbeh.2010.12.019. Sestito RS, Trindade LB, de Souza RG, Kerbauy LN, Iyomasa MM, Rosa ML. Effect of isolation rearing on the expression of AMPA glutamate receptors in the hippocampal formation. J Psychopharmacol. 2011;25(12):1720-1729. https://doi.org/10.1177/0269881110385595. Toua C, Brand L, Möller M, Emsley RA, Harvey BH. The effects of sub-chronic clozapine and haloperidol administration on isolation rearing induced changes in frontal cortical N-methyl-D-aspartate and D1 receptor binding in rats. Neuroscience. 2010;165(2):492-499. https://doi.org/10.1016/j.neuroscience.2009.10.039. Alò R, Avolio E, Mele M, Storino F, Canonaco A, Carelli A et al. Excitatory/inhibitory equilibrium of the central amygdala nucleus gates anti-depressive and anxiolytic states in the hamster. Pharmacol Biochem Behav. 2014; 118:79-86. https://doi.org/10.1016/j.pbb.2014.01.007. St JP, Petkov VV. Changes in 5-HT1 receptors in different brain structures of rats with isolation syndrome. General pharmacology. 1990;21(2):223-5. https://doi.org/10.1016/0306-3623(90)90905-2. Miachon S, Rochet T, Mathian B, Barbagli B, Claustrat B. Long-term isolation of Wistar rats alters brain monoamine turnover, blood corticosterone, and ACTH. Brain Res Bull. 1993;32(6):611-614. https://doi.org/10.1016/0361-9230(93)90162-5. Van den Berg CL, Van Ree JM, Spruijt BM, Kitchen I. Effects of juvenile isolation and morphine treatment on social interactions and opioid receptors in adult rats: behavioural and autoradiographic studies. Eur J Neurosci. 1999;11(9):3023-3032. https://doi.org/10.1046/j.1460-9568.1999.00717.x. Vanderschuren LJ, Stein EA, Wiegant VM, Van Ree JM. Social play alters regional brain opioid receptor binding in juvenile rats. Brain Res. 1995;680(1-2):148-156. https://doi.org/10.1016/0006-8993(95)00256-p. Moles A, Kieffer BL, D'Amato FR. Deficit in attachment behavior in mice lacking the mu-opioid receptor gene. Science. 2004;304(5679):1983-1986. https://doi.org/10.1126/science.1095943. Panksepp J, Herman BH, Vilberg T, Bishop P, DeEskinazi FG. Endogenous opioids and social behavior. Neurosci Biobehav Rev. 1980;4(4):473-487. https://doi.org/10.1016/0149-7634(80)90036-6. Gong JP, Onaivi ES, Ishiguro H, Liu Q, Tagliaferro PA, Brusco A, et al. Cannabinoid CB2 receptors: immunohistochemical localization in rat brain. Brain Res. 2006;1071(1):10-23. https://doi.org/10.1016/j.brainres.2005.11.035. Breivogel CS, Sim-Selley LJ. Basic neuroanatomy and neuropharmacology of cannabinoids. Int Rev Psychiatry 2009; 21:2:113-121. https://doi.org/10.1080/09540260902782760. Haj-Mirzaian A, Amini-Khoei H, Haj-Mirzaian A, Amiri S, Ghesmati M, Zahir M, et al. Activation of cannabinoid receptors elicits antidepressant-like effects in a mouse model of social isolation stress. Brain Res Bull. 2017; 130:200-210. https://doi.org/10.1016/j.brainresbull.2017.01.018. Banach M, Piskorska B, Czuczwar SJ, Borowicz KK. Nitric Oxide, Epileptic Seizures, and Action of Antiepileptic Drugs. CNS & Neurological Disorders - Drug Targets 2011;10: 808. https://doi.org/10.2174/187152711798072347. Förstermann U, Sessa WC. Nitric oxide synthases: regulation and function. Eur Heart J. 2012;33(7):829-37, 837a-837d. https://dx.doi.org/10.1093%2Feurheartj%2Fehr304. Hu Y, Wu D, Luo C, Zhu L, Zhang J, Wu H, et al. Hippocampal nitric oxide contributes to sex difference in affective behaviors. PNAS. 2012, 109 (35) 14224-14229. https://doi.org/10.1073/pnas.1207461109. Khan MI, Ostadhadi S, Zolfaghari S, Mehr SE, Hassanzadeh G, Dehpour, A et al. The involvement of NMDA receptor/NO/cGMP pathway in the antidepressant like effects of baclofen in mouse force swimming test. Neuroscience Letters. 2016; 612:52-61. https://doi.org/10.1016/j.neulet.2015.12.006. Matsumoto K, Puia G, Dong E, Pinna G. GABAA receptor neurotransmission dysfunction in a mouse model of social isolation-induced stress: Possible insights into a non-serotonergic mechanism of action of SSRIs in mood and anxiety disorders. Stress. 2007; 10:1:3-12. https://doi.org/10.1080/10253890701200997. Zlatković J, Filipović D. Chronic social isolation induces NF-κB activation and upregulation of iNOS protein expression in rat prefrontal cortex. Neurochem Int. 2013;63(3):172-179. https://doi.org/10.1016/j.neuint.2013.06.002. Haj-Mirzaian A, Amiri S, Kordjazy N, Momeny M, Razmi A, Balaei MR, et al. Lithium attenuated the depressant and anxiogenic effect of juvenile social stress through mitigating the negative impact of interlukin-1β and nitric oxide on hypothalamic-pituitary-adrenal axis function. Neuroscience. 2016; 315:271-285. https://doi.org/10.1016/j.neuroscience.2015.12.024. Larson HJ. The biggest pandemic risk? Viral misinformation. Nature 2018; 562:309. https://doi.org/10.1038/d41586-018-07034-4. Zarocostas J. How to fight an infodemic. Lancet 2020; 395:676. https://doi.org/10.1016/S0140-6736(20)30461-X. World Health Organization, 2019. Ebola Virus Disease – Democratic Republic of the Congo. Geneva, Switzerland: WHO. Available at: https://www.who.int/csr/don/28-november-2019-ebola-drc/en/ [Accessed on August 8, 2020] Times of India. Covid-19: doctors gone to collect samples attacked in Indore. Available at: https://timesofindia.indiatimes.com/videos/news/covid-19-doctors-goneto- collect-samples-attacked-in-indore/videoshow/74942153.cms; 2020 [Accessed on August 8, 2020]. Withnall A. Coronavirus: why India has had to pass new law against attacks on healthcare workers. The Independent. April 23, 2020. Semple K. “Afraid to be a nurse”: health workers under attack. The New York Times. 2020 Apr 27. The Economist. Health workers become unexpected targets during COVID-19. The Economist. May 11, 2020. Turan B, Budhwani H, Fazeli PL, Browning WR, Raper JL, Mugavero MJ, et al. How does stigma affect people living with HIV? The mediating roles of internalized and anticipated HIV stigma in the effects of perceived community stigma on health and psychosocial outcomes. AIDS Behav. 2017; 21: 283–291. https://doi.org/10.1007/s10461-016-1451-5. James PB, Wardle J, Steel A, Adams J. An assessment of Ebola-related stigma and its association with informal healthcare utilisation among Ebola survivors in Sierra Leone: a cross sectional study. BMC Public Health. 2020; 20: 182. https://doi.org/10.1186/s12889-020-8279-7. Aljazeera, 2020. Iran: Over 700 Dead after Drinking Alcohol to Cure Coronavirus. Aljazeera. Available at: https://www.aljazeera.com/ news/2020/04/iran-700-dead-drinking-alcohol-cure-coronavirus200427163529629.html. (Accessed June 4, 2020) Delirrad M, Mohammadi AB, 2020. New methanol poisoning outbreaks in Iran following COVID-19 pandemic. Alcohol Alcohol. 55: 347–348. https://doi.org/10.1093/alcalc/agaa036. Hassanian-Moghaddam H, Zamani N, Kolahi A-A, McDonald R, Hovda KE. Double trouble: methanol outbreak in the wake of the COVID-19 pandemic in Iran-a cross-sectional assessment. Crit Care. 2020; 24: 402. https://doi.org/10.1186/s13054-020-03140-w. Soltaninejad K. Methanol Mass Poisoning Outbreak: A Consequence of COVID-19 Pandemic and Misleading Messages on Social Media. Int J Occup Environ Med. 2020;11(3):148-150. https://dx.doi.org/10.34172%2Fijoem.2020.1983. Islam MS, Sarkar T, Khan SH, Kamal AM, Hasan SMM, Kabir A, et al. COVID-19–Related Infodemic and Its Impact on Public Health: A Global Social Media Analysis. Am J Trop Med Hyg. 2020; 00(0):1–9. https://doi.org/10.4269/ajtmh.20-0812. Hawryluck L, Gold W, Robinson S, Pogorski S, Galea S, Styra R. SARS control and psychological effects of quarantine, Toronto, Canada. Emerg Infect Dis. 2004;10(7):1206–1212. https://dx.doi.org/10.3201%2Feid1007.030703. Lee S, Chan LYY, Chau AAM, Kwok KPS, Kleinman A. The experience of SARS-related stigma at Amoy Gardens. Soc Sci Med. 2005; 61(9): 2038-2046. https://doi.org/10.1016/j.socscimed.2005.04.010. Yoon MK Kim SY Ko HS Lee MS. System effectiveness of detection, brief intervention and refer to treatment for the people with post-traumatic emotional distress by MERS: a case report of community-based proactive intervention in South Korea. Int J Ment Health Syst. 2016; 10: 51. https://doi.org/10.1186/s13033-016-0083-5. Reynolds DL, Garay JR, Deamond SL, Moran MK, Gold W, Styra R. Understanding, compliance and psychological impact of the SARS quarantine experience. Epidemiol Infect. 2008; 136: 997-1007. https://dx.doi.org/10.1017%2FS0950268807009156. Marjanovic Z, Greenglass ER, Coffey S. The relevance of psychosocial variables and working conditions in predicting nurses' coping strategies during the SARS crisis: an online questionnaire survey. Int J Nurs Stud. 2007; 44(6): 991-998. https://doi.org/10.1016/j.ijnurstu.2006.02.012. Bai Y, Lin C-C, Lin C-Y, Chen J-Y, Chue C-M, Chou P. Survey of stress reactions among health care workers involved with the SARS outbreak. Psychiatr Serv. 2004; 55: 1055-1057. https://doi.org/10.1176/appi.ps.55.9.1055. Ministry of Health and Family Welfare. Available at: https://www.mohfw.gov.in/pdf/Guidelinesforhomequarantine.pdf [Accessed on 25 August 2020]. Ministry of Health and Family Welfare. Available at: https://www.mohfw.gov.in/pdf/RevisedguidelinesforHomeIsolationofverymildpresymptomaticCOVID19cases10May2020.pdf [Accessed on 25 August 2020]. Ministry of Health and Family Welfare. Available at: https://www.mohfw.gov.in/pdf/AdvisoryformanagingHealthcareworkersworkinginCOVIDandNonCOVIDareasofthehospital.pdf (Accessed on 25 August 2020). Ministry of Health and Family Welfare. Available at: https://www.mohfw.gov.in/pdf/RevisedguidelinesforInternationalArrivals02082020.pdf [Accessed on 25 August 2020]. Cost of the lockdown? Over 10% of GDP loss for 18 states. Available at: https://timesofindia.indiatimes.com/india/cost-of-the-lockdown-over-10-of-gdp-loss-for-18-states/articleshow/76028826.cms [Accessed on 21 August 2020]. Jorda O, Singh SR, Taylor AM. Longer-Run Economic Consequences of Pandemics. Federal Reserve Bank of San Francisco Working Paper. 2020-09. https://doi.org/10.24148/wp2020-09. Firdaus G. Mental well‑being of migrants in urban center of India: Analyzing the role of social environment. Indian J Psychiatry. 2017; 59:164‑ https://doi.org/10.4103/psychiatry.indianjpsychiatry_272_15. National Crime Record Bureau. Annual Crime in India Report. New Delhi, India: Ministry of Home Affairs; 2018. 198 migrant workers killed in road accidents during lockdown: Report. Available at: https://www.hindustantimes.com/india-news/198-migrant-workers-killed-in-road-accidents-during-lockdown-report/story-hTWzAWMYn0kyycKw1dyKqL.html [Accessed on 25 August 2020]. Qiu H, Wu J, Hong L, Luo Y, Song Q, Chen D. Clinical and epidemiological features of 36 children with coronavirus disease 2019 (COVID-19) in Zhejiang, China: an observational cohort study. Lancet Infect Dis. 2020; 20:689-96. https://doi.org/10.1016/S1473-3099(20)30198-5. Dalton L, Rapa E, Stein A. Protecting the psychological health of through effective communication about COVID-19. Lancet Child Adolesc Health. 2020;4(5):346-347. https://doi.org/10.1016/S2352-4642(20)30097-3. Centre for Disease Control. Helping Children Cope with Emergencies. Available at: https://www.cdc.gov/childrenindisasters/helping-children-cope.html [Accessed on 25 August 2020]. Liu JJ, Bao Y, Huang X, Shi J, Lu L. Mental health considerations for children quarantined because of COVID-19. Lancet Child & Adolesc Health. 2020; 4(5):347-349. https://doi.org/10.1016/S2352-4642(20)30096-1. Sprang G, Silman M. Posttraumatic Stress Disorder in Parents and Youth After Health-Related Disasters. Disaster Med Public Health Prep. 2013;7(1):105-110. https://doi.org/10.1017/dmp.2013.22. Rehman U, Shahnawaz MG, Khan NH, Kharshiing KD, Khursheed M, Gupta K, et al. Depression, Anxiety and Stress Among Indians in Times of Covid-19 Lockdown. Community Ment Health J. 2020:1-7. https://doi.org/10.1007/s10597-020-00664-x. Cao W, Fang Z, Hou, Han M, Xu X, Dong J, et al. The psychological impact of the COVID-19 epidemic on college students in China. Psychiatry Research. 2020; 287:112934. https://doi.org/10.1016/j.psychres.2020.112934. Wang C, Zhao H. The Impact of COVID-19 on Anxiety in Chinese University Students. Front Psychol. 2020; 11:1168. https://dx.doi.org/10.3389%2Ffpsyg.2020.01168. Kang L, Li Y, Hu S, Chen M, Yang C, Yang BX, et al. The mental health of medical workers in Wuhan, China dealing with the 2019 novel coronavirus. Lancet Psychiatry 2020;7(3): e14. https://doi.org/10.1016/s2215-0366(20)30047-x. Lai J, Ma S, Wang Y, Cai Z, Hu J, Wei N, et al. Factors associated with mental health outcomes among health care workers exposed to coronavirus disease 2019. JAMA Netw Open 2020;3(3): e203976. https://doi.org/10.1001/jamanetworkopen.2020.3976. Lancee WJ, Maunder RG, Goldbloom DS, Coauthors for the Impact of SARS Study. Prevalence of psychiatric disorders among Toronto hospital workers one to two years after the SARS outbreak. Psychiatr Serv. 2008;59(1):91-95. https://dx.doi.org/10.1176%2Fps.2008.59.1.91. Tam CWC, Pang EPF, Lam LCW, Chiu HFK. Severe acute respiratory syndrome (SARS) in Hongkong in 2003: Stress and psychological impact among frontline healthcare workers. Psychol Med. 2004;34 (7):1197-1204. https://doi.org/10.1017/s0033291704002247. Lee SM, Kang WS, Cho A-R, Kim T, Park JK. Psychological impact of the 2015 MERS outbreak on hospital workers and quarantined hemodialysis patients. Compr Psychiatry. 2018; 87:123-127. https://dx.doi.org/10.1016%2Fj.comppsych.2018.10.003. Koh D, Meng KL, Chia SE, Ko SM, Qian F, Ng V, et al. Risk perception and impact of severe acute respiratory syndrome (SARS) on work and personal lives of healthcare workers in Singapore: What can we learn? Med Care. 2005;43(7):676-682. https://doi.org/10.1097/01.mlr.0000167181.36730.cc. Verma S, Mythily S, Chan YH, Deslypere JP, Teo EK, Chong SA. Post-SARS psychological morbidity and stigma among general practitioners and traditional Chinese medicine practitioners in Singapore. Ann Acad Med Singap. 2004; 33(6):743e8. Yeung J, Gupta S. Doctors evicted from their homes in India as fear spreads amid coronavirus lockdown. CNN World. 2020. Available at: https://edition.cnn.com/2020/03/25/asia/india-coronavirus-doctors-discrimination-intl-hnk/index.html. [Accessed on 24 August 2020] Violence Against Women and Girls: the Shadow Pandemic. UN Women. 2020. May 3, 2020. Available at: https://www.unwomen.org/en/news/stories/2020/4/statement-ed-phumzile-violence-against-women-during-pandemic. [Accessed on 24 August 2020]. Gearhart S, Patron MP, Hammond TA, Goldberg DW, Klein A, Horney JA. The impact of natural disasters on domestic violence: an analysis of reports of simple assault in Florida (1999–2007). Violence Gend. 2018;5(2):87–92. https://doi.org/10.1089/vio.2017.0077. Sahoo S, Rani S, Parveen S, Pal Singh A, Mehra A, Chakrabarti S, et al. Self-harm and COVID-19 pandemic: An emerging concern – A report of 2 cases from India. Asian J Psychiatr 2020; 51:102104. https://dx.doi.org/10.1016%2Fj.ajp.2020.102104. Ghosh A, Khitiz MT, Pandiyan S, Roub F, Grover S. Multiple suicide attempts in an individual with opioid dependence: Unintended harm of lockdown during the COVID-19 outbreak? Indian J Psychiatry 2020; [In Press]. The Economic Times. 11 Coronavirus suspects flee from a hospital in Maharashtra. March 16 2020. Available at: https://economictimes.indiatimes.com/news/politics-and-nation/11-coronavirus-suspects-flee-from-a-hospital-in-maharashtra/videoshow/74644936.cms?from=mdr. [Accessed on 23 August 2020]. Xiang Y, Yang Y, Li W, Zhang L, Zhang Q, Cheung T, et al. Timely mental health care for the 2019 novel coronavirus outbreak is urgently needed. The Lancet Psychiatry 2020;(3):228–229. https://doi.org/10.1016/S2215-0366(20)30046-8. Van Bortel T, Basnayake A, Wurie F, Jambai M, Koroma A, Muana A, et al. Psychosocial effects of an Ebola outbreak at individual, community and international levels. Bull World Health Organ. 2016;94(3):210–214. https://dx.doi.org/10.2471%2FBLT.15.158543. Kumar A, Nayar KR. COVID 19 and its mental health consequences. Journal of Mental Health. 2020; ahead of print:1-2. https://doi.org/10.1080/09638237.2020.1757052. Gupta R, Grover S, Basu A, Krishnan V, Tripathi A, Subramanyam A, et al. Changes in sleep pattern and sleep quality during COVID-19 lockdown. Indian J Psychiatry. 2020; 62(4):370-8. https://doi.org/10.4103/psychiatry.indianjpsychiatry_523_20. Duan L, Zhu G. Psychological interventions for people affected by the COVID-19 epidemic. Lancet Psychiatry. 2020;7(4): P300-302. https://doi.org/10.1016/S2215-0366(20)30073-0. Dubey S, Biswas P, Ghosh R, Chatterjee S, Dubey MJ, Chatterjee S et al. Psychosocial impact of COVID-19. Diabetes Metab Syndr. 2020; 14(5): 779–788. https://dx.doi.org/10.1016%2Fj.dsx.2020.05.035. Wright R. The world's largest coronavirus lockdown is having a dramatic impact on pollution in India. CNN World; 2020. Available at: https://edition.cnn.com/2020/03/31/asia/coronavirus-lockdown-impact-pollution-india-intl-hnk/index.html. [Accessed on 23 August 2020] Foster O. ‘Lockdown made me Realise What’s Important’: Meet the Families Reconnecting Remotely. The Guardian; 2020. Available at: https://www.theguardian.com/keep-connected/2020/apr/23/lockdown-made-me-realise-whats-important-meet-the-families-reconnecting-remotely. (Accessed on 23 August 2020) Bilefsky D, Yeginsu C. Of ‘Covidivorces’ and ‘Coronababies’: Life During a Lockdown. N. Y. Times; 2020. Available at: https://www.nytimes.com/2020/03/27/world/coronavirus-lockdown-relationships.html [Accessed on 23 August 2020]